ANALISIS EFEKTIVITAS MODEL PENUMBUHAN KLASTER INDUSTRI KECIL BERBASIS AGRIBISNIS ( Studi Kasus Industri Kecil Sapu Glagah Kabupaten Purbalingga ) - Indi Sutopo (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
This research applied to survey methode, with the three subdistrict are Bojongsari with  Kajongan and Brobot as villages sample, Karangjambu with Kajongan and Brobot villages samples, Karangreja subdistrict with  Karangreja and Gondang as village sample. The multivariet and regression methode be uses as tools of analysis to founds influences factor of the production and industrial productivity and so on will be use as arranging small industrial sapu glagah model. The analysis can be found that the sapu glagah small industrial have developed, but no coorporations in group efectivelly, inter coorporation of  firms, inter coorporation of productions, and market operations. Some time often are competitions inter firms in raw material buying and competition in market. The dominant factor of the small industrial cluster sapu glagah progress are the institutional, industrial productivity and the new technology iquipment and mechinerry. The initial of govement assistancy and other institutionals are make the group or institutional be come the firms sturdy, reinforce the role of dominant factors firms progrresion with the group empowerment. Keywords : Typology, Cluster, Small Industries, Agribusiness